Pregnancy in Ellis Van Creveld syndrome women: a rare case report - N., Sunanda; Aisha, Talath (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Ellis Van Creveld (EVC) syndrome also known as chondroectodermal dysplasia is a rare genetic disorder characterized by congenital heart defect, short ribs, polydactyly, dwarfism, deformed teeth and genu valgum. It is a rare disease with approximately 150 cases reported worldwide. The exact prevalence in India is not known, but the syndrome seems more common among Amish population of Pennsylvania in the United States of America (USA). Heart defects occur in about 60% of cases. Cognitive and motor development is normal. It shows autosomal recessive trait with variable expression. The patients with this syndrome rarely survive into adulthood but here we report a case of 25 years old pregnant lady with Ellis Van Creveld syndrome.